PROBLEMS OF ENGLISH STUDENTS FOLLOWING THE LANGUAGE TESTING CLASS SEMESTER IV ENGLISH EDUCATION PROGRAM UNIVERSITY MUHAMMADIYAH BENGKULU - Gita Aprillasis (Berajah Journal, 2022)
This study aims to determine the problems of students in the learning process following the class language test. The method used by researchers in this study is a qualitative method with a descriptive approach. The data of this study were 20 respondents who filled out the questionnaire, namely the fourth semester students 5% felt bored, and 55% stated that the material was too much, 5% stated that they were not interested in LT learning, 30% were able to master, then 50% felt bored receiving the material, then 50% sometimes takes time to understand the material, and 75%. LT lecturers provide assistance when experiencing difficulties, and 55% of statements can sometimes conclude material and also provide interviews, it turns out that there are internal and external factors. internal factors from interviews conducted by understanding the material, Easy to forget, do you need difficult material, Difficult to concentrate and external factors found Too much material and material delivery too fast.